Trend Penghilangan Nyawa Diri dalam Kalangan Masyarakat - Nasir, Raihan; Abdullah, Amalina Amalin; Azlisham, Nur Afiqah Nasuha; Abdullah, Alysha; Sukor, Nurul Aliyah Izyan Abd (Yayasan Putroe Ceudah Aceh, 2025)
This study examines the rising trend of death by suicidal, and acts of killing and death punishment, from the perspective of Islamic philosophy and education. Using qualitative and a textual analysis approach, interviews were conducted with the families and close friends of suicide victims. Furthermore, the data is analyzed with a thematic analysis model. The study evaluates the moral and ethical justifications behind the act of death by suicidal according to major philosophical schools western philosophy and Islamic philosophy. It further explores how socio-cultural factors, the pressures of modern life, and shifts in human values influence society’s perception of life and death. The findings reveal that the trend of life-taking not only reflects the failure of social systems but also signifies a crisis of meaning in modern human life due to a lack of true understanding of the concepts of life and death. The study suggests the need for a more emphathetic and holistic philosophical approach in addressing this issue, to uphold human values and preserve the objectives of Shariah (Maqasid al-Syariah), particularly in preservation of life (hifz al-nafs). So that the trend of loss of life among the people in Malaysia can be overcome well.